2017
DOI: 10.1007/s10646-017-1768-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of various insecticides used for management of Asian citrus psyllid, Diaphorina citri in Florida citrus, against honey bee, Apis mellifera

Abstract: The Asian citrus psyllid, Diaphorina citri Kuwayama (Hemiptera: Liviidae), is a major pest of citrus trees worldwide. A wide variety of insecticides are used to manage D. citri populations within citrus groves in Florida. However, in areas shared by citrus growers and beekeepers the use of insecticides may increase the risks of Apis mellifera  L. (Hymenoptera: Apidae) loss and contaminated honey. The objective of this research was to determine the environmental toxicity of insecticides, spanning five different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 33 publications
1
13
0
6
Order By: Relevance
“…Our results shown that the pyrethrum extract is effective on phenoloxidase activity at 0.6 mg/ml level (Figure 1). The data obtained from our study confirms the results of Chen et al (2017). The injection of pyrethrum extract at the level of 0.6 mg/ml is inducing PO formation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results shown that the pyrethrum extract is effective on phenoloxidase activity at 0.6 mg/ml level (Figure 1). The data obtained from our study confirms the results of Chen et al (2017). The injection of pyrethrum extract at the level of 0.6 mg/ml is inducing PO formation.…”
Section: Discussionsupporting
confidence: 91%
“…According to Chen et al (2017), fenpropathrin, a type of pyrethrin, also causes an increase in total PO activity in honey bee (Apis mellifera). This increase is due to the moderate inhibition of fenpropatrin on the diphenolase activity of tyrosinase (Tang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These results are important because of the paucity of information on invertebrate immunity and atrazine. While the effects of atrazine on vertebrate immunity have received a great deal of attention ( Rohr and McCoy 2010 , Sifkarovski et al 2014 ) and several authors have documented effects of other agrochemicals on invertebrate immune systems ( Chen et al 2017 , Kalita et al 2017 , Zhu et al 2017 ), we did not find studies examining the impact of atrazine on invertebrate immune systems, despite the high levels of use in the United States ( Atwood and Paisley-Jones 2017 ).…”
Section: Discussionmentioning
confidence: 61%
“…Immune stress from environmental contaminants is likely to place additional strain on this cost/benefit system ( Guedes et al 2016 ). A number of authors have documented the impact of pesticides on economically important terrestrial species ( Chen et al 2017 , Kalita et al 2017 , Zhu et al 2017 ). However, fewer studies have focused on immunological impacts of pesticides on nontarget insect species, particularly in the aquatic environment.…”
mentioning
confidence: 99%
“…No entanto, apesar dessas recomendações serem, atualmente, o que melhor se pode fazer para o manejo adequado do HLB, o uso intensivo de agroquímicos pode ser perigoso para o meio ambiente, contaminando o solo e a água (Ribas & Matsumura, 2009) e causando desequilíbrio ao ecossistema, como a morte das abelhas evidenciada por Chen et al (2017a). As aplicações excessivas destes produtos químicos com o mesmo modo de ação podem levar à forte pressão de seleção de resistência do vetor (Yamamoto et al, 2009;Tiwari et al, 2011;Boina & Bloomquist, 2015).…”
Section: Manejo Cultural E Genético Do Hlbunclassified